Določitev koeficienta upora potopljenega telesa z uporabo metode SPH - Novak, Gorazd (Acta hydrotechnica, 2019)
The open-source software DualSPHysics was used so set up a three-dimensional model of a free-surface water flow in a narrow horizontal open channel with a rectangular cross section, and to determine the forces acting on various submerged fixed objects. Simulations included a sphere, a cube, and a composite capsule-like object made out of three basic bodies. Objects were located in the channel's central axis at various distances from the channel bed, and were exposed to various flow velocities. Calculating the hydrodynamic forces acting upon the objects resulted in longitudinal forces increasing with the square of the velocity, transverse forces equal to zero, and constant vertical forces. The calibrated and validated model was used to evaluate the drag coefficient of the submerged composite capsule-like object. This research reveals certain limitations of DualSPHysics and facilitates future improvements of the code and the upgrade of studies related to vertical slot fishways.
Keywords: 3-D model; CFD; DualSPHysics; force; FSI; gradbeništvo; hidrodinamika; hidrotehnika; hydrodynamics; potopljeno telo; sile; SPH; submerged body